2020
DOI: 10.1155/2020/3401605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Analysis of Percutaneous Endoscopic Lumbar Discectomy Combined with PEEK Rods for Giant Lumbar Disc Herniation: A Randomized Controlled Study

Abstract: Objective. This study describes a randomized controlled trial that assesses percutaneous endoscopic lumbar discectomy (PELD) combined with a polyetheretherketone (PEEK) rod in patients with GLDH (herniation affecting 50% of the sagittal diameter of the spinal canal) and reports the 2-year follow-up outcome. Methods. In all, 243 patients were randomly assigned to undergo PELD or PELD combined with a PEEK rod by generating random numbers with a random number generator. Clinical outcome data, including the numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Full text of the remaining 52 articles was carefully evaluated. 9 studies that met the inclusion and exclusion criteria were eventually included in this meta-analysis [22][23][24][25][26][27][28][29][30]. A total of 2505 patients were included in this analysis, and the basic characteristics of the included study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Full text of the remaining 52 articles was carefully evaluated. 9 studies that met the inclusion and exclusion criteria were eventually included in this meta-analysis [22][23][24][25][26][27][28][29][30]. A total of 2505 patients were included in this analysis, and the basic characteristics of the included study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our research team has extensive experience in endoscopic procedures using full spinal endoscopy for degenerative spinal diseases [19][20][21][22][23]. We were aware of the various advantages of endoscopy, such as visualization of the operation, minimal surgical trauma, and rapid recovery, so we began to apply our endoscopic technique to benign spinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 2 According to statistics, the incidence of huge lumbar disc herniation (HLDH) accounts for 8 to 22% of all cases of LDH. 3 As a special type of lumbar disc herniation, HLDH usually results in more severe back and leg pain, as well as often associated with neurological deficits, compared to general LDH. 4 , 5 The long-term clinical outcomes of Spine Patient Outcomes Research Trial (SPORT) suggested significantly greater improvement in pain, function and satisfaction in operative group compared to nonoperative group.…”
Section: Introductionmentioning
confidence: 99%